Alterations in biochemical profiles of patients with severe COVID-19 pneumonia: Analysis of repeated laboratory tests - Demirtakan, Türker; Çakmak, Fatih; Meten, Esra; Bener, Abdülbari; Doğan, Serkan (Kare Publishing, 2023)
Objective: This study was initiated to show the changes in the biochemical profile and identify the mortality risk factors of patients with severe coronavirus disease-19 (COVID-19) pneumonia. Materials and Methods: This study was designed as non-interventional and cohort research. Demographic and clinical data were retrospectively obtained from paper-based documents and electronic health records. Complete blood counts, inflammatory markers, liver, and kidney function tests, and coagulation profiles were recorded 3 times. Two-way ANOVA for repeated measures was used to analyze for continuous dependent variables. Binary logistic regression analysis was performed to determine in-hospital mortality risk factors. Results: Two hundred and fifty-two adult patients with severe COVID-19 pneumonia enrolled in our study – 15.8% of patients died during hospitalization. The mortality rate was 57.5% for those over 65 years of age. 61.9% of patients had at least one coexisting disease. We revealed hemoglobin, leukocyte, lymphocyte, platelet, C-reactive protein, procalcitonin, d-dimer, aspartate aminotransferase, and alanine aminotransferase, lactate dehydrogenase, creatinine, and ferritin were significantly changing within the time and also between survivors and non-survivors. Conclusion: The study showed that blood cell counts, coagulation profiles, liver and kidney function tests, and inflammatory markers deteriorated in non-survivor COVID-19 patients. Patients with shortness of breath, history of congestive heart failure, coronary artery disease, dementia, chronic renal disease, higher Charlson comorbidity index score, the need for invasive mechanic ventilation, presence of acute respiratory distress syndrome, and intensive care unit admission are more vulnerable to death.
Keywords: Biochemical Profile; COVID-19; Mortality; Severe Pneumonia